Preoperative Treatment of Severe Diabetes Mellitus and Hypertension Mitigates Healthcare Disparities and Prevents Adverse Postoperative Discharge to a Nursing Home. Issue 3 (28th September 2022) - Wachtendorf, Luca J.; Azimaraghi, Omid; Rangasamy, Valluvan; Sane, Miheer; Subramaniam, Balachundhar; Vazquez, Rafael; Wongtangman, Karuna; Houle, Timothy T.; Bellin, Eran Y.; Akeju, Oluwaseun; Straker, Tracey; Chambers, Terry-Ann T.; et al.
Abstract : Objective: To evaluate whether patients of Black race are at higher risk of adverse postoperative discharge to a nursing home, and if a higher prevalence of severe diabetes mellitus and hypertension are contributing. Background: It is unclear whether a patient's race predicts adverse discharge to a nursing home after surgery, and if preexisting diseases are contributing. Methods: A total of 368, 360 adults undergoing surgery between 2007 and 2020 across 2 academic healthcare networks in New England were included. Patients of self-identified Black or White race were compared. The primary outcome was postoperative discharge to a nursing facility. Mediation analysis was used to examine the impact of preexisting severe diabetes mellitus and hypertension on the primary association. Results: In all, 10.3% (38, 010/368, 360) of patients were Black and 26, 434 (7.2%) patients were discharged to a nursing home. Black patients were at increased risk of postoperative discharge to a nursing facility (adjusted absolute risk difference: 1.9%; 95% confidence interval: 1.6%–2.2%; P <0.001). A higher prevalence of preexisting severe diabetes mellitus and hypertension in Black patients mediated 30.2% and 15.6% of this association. Preoperative medication-based treatment adherent to guidelines in patients with severe diabetes mellitus or hypertension mitigated the primary association ( P -for-interaction <0.001). The same pattern of effect mitigation by pharmacotherapy was observed for the endpoint 30-day readmission. Conclusions: Black race was associated with postoperative discharge to a nursing facility compared to White race. Optimized preoperative assessment and treatment of diabetes mellitus and hypertension improves surgical outcomes and provides an opportunity to the surgeon to help eliminate healthcare disparities.